The inglorious arts of peace : exhibitions in Canadian society during the nineteenth century - Heaman, E. A. (Elsbeth A.), 1964- (University of Toronto Press, 1999)
"The exhibition was one of the great nineteenth-century projects for improving the world. Combining the Victorian virtues of communication, cooperation, and competition, it promised to advertise the choice products of civilization to a receptive public. The Inglorious Arts of Peace is the first comprehensive look at the history of these cultural extravaganzas in Canada." "Heaman examines the ways in which British North America was advertised at home and abroad in the pursuit of productivity, markets, capital, and immigrants, and evaluates the exhibitions' impact on private industry, the government, and Canadian identity. She also considers the participation of women and native peoples at local and international exhibits, showing how they transcended the limited spheres of representation imposed upon them. The Inglorious Arts of Peace will appeal to those interested in Canadian history and in the historical constructions of gender and race."--Jacket